Natural carotenoid pigments from 6 chlorophyta freshwater green algae species cell culture as potential halal food colorants - Noh, Nur Hidayah; Othman, Rashidi; Jamaludin, Mohammad Aizat (2015)
Nowadays, halal products are gaining wider recognition as a new benchmark for safety and quality assurance. As a consequence the commercial development of microalgae are established due to their high value chemicals, for examples, β-carotene, astaxanthin, phycobilin pigments and algal extracts for cosmaceuticals products. Therefore, many researchers have gained interest to study the potential of microalgae as new valuable chemicals and other products sources. The aim of the research is to explore new sources of pigments to be used as halal food colorants. This quest is not only directed in finding natural alternatives for synthetic dyes, but also to discover new taxons for the carotenoid production. Thus, there is a solid need to investigate the potential of natural pigments particularly carotenoids in microalgae to be fully utilised and commersialised especially in halal market, health advantages, food products and dye technology. A total of 6 species were evaluated for quantitative and qualitative carotenoid composition namely Chlorella fusca, Chlorella vulgaris, Selenastrum capricornutum, Pandorina morum, Botryococcus sudeticus and Chlorococcum sp. The main carotenoids identified in all species through HPLC analysis were lutein, β-cryptoxanthin and β-carotene. The ratio of these carotenoids varies between species. Lutein was detected substantially higher in Chlorella fusca (69.54±11.29µg/g DW); β-cryptoxanthin in Pandorina morum species (1.24±0.33 µg/g DW) whereas β-carotene in Chlorella vulgaris (18.42±9.2 ug/g DW). The significant outcome of the research will be new findings of new natural carotenoid pigment sources as potential food colorants and bioactive compounds which can be beneficial to halal health promoting products industry.